Anesthesia for a parturient with intraneural perineurioma: A case report. Issue 49 (December 2017) - Li, Jiao; Zeng, Hong; Li, Zhengqian; Wang, Jun
Abstract: Rationale: Intraneural perineurioma is an extremely rare form of peripheral nerve sheath tumor; and the anesthetic management of a parturient with intraneural perineurioma, especially affecting spinal roots and nerves of extremities, is very rare. Patient concerns: A 28-year-old woman was referred to the hospital at 37+5 weeks' gestation, presenting with a 10-year history of paroxysmal acroanesthesia and aching with distal limbs. Diagnoses: Based on the biopsy results, including immunohistochemical and electron microscopic findings, and molecular studies, her condition was diagnosed as intraneural perineurioma. Interventions: The size of pelvic nervous masses gradually increased with pregnancy. A scheduled elective cesarean section under general anesthesia was concluded for the patient under preoperative multidisciplinary consultation with anesthesiologist, neonatologist, and neurologist. Outcomes: The patient and the neonate were discharged smoothly on the fourth postoperative day. During a 6-month follow-up period, no new neurologic complication was observed. Lessons: To our knowledge, this is the first case report that documented the anesthetic management for a parturient with intraneural perineuroma. Careful preconception care and multidisciplinary assessment are essential to achieve optimal reproductive outcomes.